Talented, Yet Seen With Suspicion: Surveillance of International Students and Scholars in the United States - Allen, Ryan; Bista, Krishna (Journal of International Students, 2021)
The attacks of September 11, 2001, put terrorism at the forefront of the American political landscape. Donald Trump played into these fears of terrorism through his political rhetoric during his presidency, particularly targeting international students as “threats” to the nation. However, we argue that the labeling of international students as security threats was not started after 9/11 nor invented by Trump. Through historical records and accounts across decades of policies related to this issue, we seek to answer two questions: How has the U.S. government monitored visa policies and programs for international students? How have U.S. national policies evolved to view international students as national security threats? We find that mistrust of this population has been embedded throughout U.S. immigration history and that federal tracking policies emerged incrementally from long-held security concerns. We discuss why the entire population of international students should not be scapegoated due to fear.